POLITIK PEMBERITAAN JOKOWI DI MEDIA MASSA (Analisis Framing Politik Pemberitaan Jokowi di Majalah Tempo Edisi Januari-Juli 2014) - Wibisono, Irawan (Transformasi, 2015)
Joko Widodo, or more commonly known as Jokowi won the presidential elections of the Republic of Indonesia on 9 July 2014. Tempo magazine became one of the media coverage about this Jokowi. Research on the Tempo Magazine framing against Jokowi is intended to determine how the viewpoint Tempo in reporting Jokowi. The method used is content analysis of media texts that use the paradigm of constructionism with qualitative research methods. The object of the research is the issue of Tempo Magazine in January to July 2014. The data analysis technique used is framing analysis model Zhongdang Pan and Kosicki. The analysis showed Tempo has a frame that Jokowi deserves to be president because he is not the person who is born of the main circle of political parties.Keyword: mass media political campaigns